EL NIVEL DE INGRESOS GENERADOS POR LA ACTIVIDAD AGRÍCOLA Y SU INCIDENCIA EN LAS CONDICIONES DE VIDA DE LAS FAMILIAS DEL CANTÓN GONZANAMÁ AÑO 2013 - Briceño Briceño, María Cristina (2015)
The analysis of the income generated by agricultural activity in the canton Gonzanamá, has a fundamental value in the lives of families, since it is one of the sectors in which its economy is based. However, the families of the canton face various difficulties, ranging from the lack of rain, and pests that requires them to use pesticides, and the fact of not using enough fertilizer, resulting in low productivity. Faced with this problem an investigation into "The level of income generated by agricultural activity and its impact on the living conditions of the families of Gonzanamá canton 2013", in which the main crops, sale prices are investigated was raised, socioeconomic conditions, the main problems of the cantonal agricultural activity, and thus determine the income and know the living conditions of the families of the canton. The proposed general objective was to analyze the level of income generated by agricultural activity and its impact on the living conditions of families in the canton Gonzanamá, 2013. The results show that the income generated by agriculture are limited by the extent of the land, crop type and do not outweigh the hard work done in this activity, what would be the main reason why they are becoming less those engaged in it. In conclusion income earned by families engaged in traditional farming and technologically in small properties, it does not allow them to have enough income to cover their basic needs, mainly due to low productivity and small production volumes. Keywords: Agricultural, productivity, living conditions, Main crop income